Pengembangan Sistem Informasi Penjualan Berbasis Web untuk Optimalisasi Pendapatan UMKM Café Travel - Calandra Alencia Haryani; Immanuel Christian Hirani; Heri Heri; Arnold Aribowo; Andree E. Widjaja (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid growth of technology has driven economic transformation towards the digital era, including in the Micro, Small, and Medium Enterprises (MSME) sector. Café Travel, an MSME selling pizza, coffee, and soft drinks, has experienced a revenue decline since the COVID-19 pandemic due to limited market reach and manual sales data management. This situation has led to a high risk of recording errors and restricted product innovation. This Community Service activity aims to develop a web-based sales information system to improve operational efficiency and expand market reach. The system development was carried out using the Rapid Application Development (RAD) methodology with a prototyping approach, supported by business process modeling using Business Process Modeling Notation (BPMN) and system documentation using Unified Modeling Language (UML). The developed information system has pizza order customization features, integrated sales processing, and structured sales data management. It was built using the PHP programming language and the Laravel 11 framework. Implementing this system is expected to improve the accuracy of sales record-keeping, accelerate transaction processes, and facilitate customers' customizing menu orders according to their preferences.